Conflict Management of Directors’ School in Bang Bo Group 2 under Samutprakan Primary Educational Service Area Office 2: - Duangdee, Laksika; Watcharathanakhom, Kampanat; Noymanee, Niwat (RPU Journal of Business Administration, 2022)
This research aims to 1) study about conflict management levels of school administrators in Bang Bo school group 2 under the Samut Prakan Primary Educational Service Area Office 2, 2) to compare management approaches for conflict management levels of school administrators in Bang Bo school group 2 under the Samut Prakan Primary Educational Service Area Office 2 which divided by gender, age, education and work experience, respectively. Then population of such research are consisted of teachers under Bang Bo school group 2 in 2021 about 148 persons. The results were as follows 1) The conflict management levels of school administrators in Bang Bo school group 2 is in moderate level in overall, then determining in each factors found that first averaged factor was compromising is in the highest ranking and followed by obliging and the last one was dominating that are in moderate level as same. 2) The conflict management levels of school administrators in Bang Bo school group 2, which divided by gender, age, education and work experience found that 2.1) The conflict management levels of school administrators in Bang Bo school group 2, which divided by gender, age and work experience there were no difference. 2.2) The conflict management levels of school administrators in Bang Bo school group 2, which divided by education there was statistically significant difference.